Resolution to Inflammation: Its Role in Reducing Fibrosis and Tissue Repair - Anna Meiliana; Andi Wijaya (The Indonesian Biomedical Journal, 2023)
BACKGROUND: Many chronic disorders, including vascular diseases, metabolic syndrome, and neurological diseases, are known to share a common factor of excessive inflammation. It takes a lot of energy to heal damaged tissue, which is a complicated process. The outcome is often suboptimal, with some degree of fibrosis, depending on the tissue's ability to regenerate and the strength of the inflammatory response. We may get new insights into disease causation and therapeutic strategies by better understanding endogenous regulatory points within the inflammatory response.CONTENT: Despite of the benefit in raising an inflammatory response, it also have unfavourable effects. Unresolved inflammation can over accumulate collagenous connective tissue and induce fibrosis, promote tissue dysfunction, and finally organ failure. Currently, the resolution of inflammation was described in terms of contemporary molecules as a different mechanisms from anti-inflammatory, since in resolution, the pathogen and apoptotic cells crumbs will be cleared and the macrophages will set back the tissue homeostasis. An active transition in the mediators that predominate in exudates occurs in conjunction with the remission of inflammation. These groups of inborn pro-resolution named resolvins, maresins, and protectins work to reduce inflammation by triggering certain pathways that support homeostasis rather than by suppressing the immune system.SUMMARY: The resolution of inflammation, once believed to be a passive process, is now understood to entail active biochemical programs that allow inflamed tissues to regain equilibrium. In this review, we spotlight the resolution to inflammation as a strategy to prevent tissue fibrosis and hinder the organ damage.KEYWORDS: inflammation, resolution, fibrosis, wound healing, specialized pro-resolving mediators